Advances in kidney disease: pathogenesis and therapeutic targets - Vincent Boima; Alex Baafi Agyekum; Khushali Ganatra; Francis Agyekum; Edward Kwakyi; Jalil Inusah; Elmer Nayra Ametefe; Dwomoa Adu (Frontiers in Medicine)
Chronic kidney disease (CKD) is a global public health issue characterized by progressive loss of kidney function, of which end-stage kidney disease (ESKD) is the last stage. The global increase in the prevalence of CKD is linked to the increasing prevalence of traditional risk factors, including obesity, hypertension, and diabetes mellitus, as well as metabolic factors, particularly insulin resistance, dyslipidemia, and hyperuricemia. Mortality and comorbidities, such as cardiovascular complications, rise steadily as kidney function deteriorates. Patients who progress to ESKD require long-term kidney replacement therapy, such as transplantation or hemodialysis/peritoneal dialysis. It is currently understood that a crucial aspect of CKD involves persistent, low-grade inflammation. In addition, increased oxidative and metabolic stress, endothelial dysfunction, vascular calcification from poor calcium and phosphate metabolism, and difficulties with coagulation are some of the complex molecular pathways underlying CKD-related and ESKD-related issues. Novel mechanisms, such as microbiome dysbiosis and apolipoprotein L1 gene mutation, have improved our understanding of kidney disease mechanisms. High kidney disease risk of Africa has been linked to APOL1 high-risk alleles. The 3-fold increased risk of ESKD in African Americans compared to European Americans is currently mainly attributed to variants in the APOL1 gene in the chromosome 22q12 locus. Additionally, the role of new therapies such as SGLT2 inhibitors, mineralocorticoid receptor antagonists, and APOL1 channel function inhibitors offers new therapeutic targets in slowing down the progression of chronic kidney disease. This review describes recent molecular mechanisms underlying CKD and emerging therapeutic targets.